Spontaneous Neurological Recovery of Patients with Acute Traumatic Spinal Cord Injuries (ATSCI) without Intervention the Injured Cord” - El Masri, W.S. (International Journal of Orthopedics and Rehabilitation, 2021)
Acute traumatic spinal cord injuries (ATSCI) are life threatening and life changing events. With good Active Physiological Conservative Management (APCM) of the injured spine and the systemic effects of cord damage to prevent further mechanical and non-mechanical damage of the cord the majority of patients make some spontaneous neurological recovery (SNR). The magnitude and extent of this recovery depends on the initial degree and topographical sparing of sensory and sensory-motor tracts functions at and below the Zone of Partial Preservation (ZPP).